Single-Stage Endovascular Treatment of Severe Cranial Artery Stenosis Coexisted With Ipsilateral Distal Tandem Intracranial Aneurysm - Ni, Hongyang; Zhong, Zhihong; Zhu, Jun; Jiang, Hong; Hu, Jinqing; Lin, Dong; Bian, Liuguan (Frontiers in Neurology, 2022)
Objective The coexistence of severe cranial artery stenosis and ipsilateral distal tandem intracranial aneurysm is an unusual phenomenon. Currently, there is no consensus to provide treatment guidelines for concomitant lesions. This study aims to evaluate the safety and effectiveness of single-stage endovascular treatment in patients under this special condition. Methods We illustrated a case series of 10 patients with the coexistence of severe cranial artery stenosis and ipsilateral distal tandem intracranial aneurysm in our hospital. And a systematic PubMed search of English-language literature published between 1990 and 2021 was carried out using the keywords: “(carotid OR vertebral OR subclavian artery stenosis) AND (aneurysm) AND (coincident OR coexist OR concomitant OR simultaneous OR ipsilateral).” Clinical information, including age, gender of the patients, as well as symptoms (artery stenosis or aneurysm), localization of artery stenosis and aneurysm, treatment, and outcome, were collected and analyzed. Results In the majority of the patients, symptoms were attributed to severe artery stenosis, and the coexisted lesions were located in the anterior circulation system. Most patients achieved an excellent clinical outcome, and no death was observed. No differences were found in a prognosis between single-stage or multiple-stage endovascular treatment. Conclusions A single-stage endovascular procedure is technically feasible and effective to treat the coexistence of severe cranial artery stenosis and ipsilateral distal tandem intracranial aneurysm in the anterior circulation as well as in the posterior circulation.